Răspuns :
a ) 2 ( x + 3 ) = 8
2x + 6 = 8
2x = 8 - 6
2x = 2
x = 1
b ) 4 ( x + 1 ) + 3 = 35
4 x + 4 + 3 = 35
4 x = 35 - 7
4 x = 28
x = 7
c ) 5 ( 2 x + 3 ) + 1 = 76
10 x + 15 + 1 = 76
10 x = 76 - 16
10 x = 60
x = 6
D ) 4 ( 2 x + 4 ) -10 = 54
8 x + 16 -10 = 54
8 x = 54 - 6
8 x = 48
x = 6
2x + 6 = 8
2x = 8 - 6
2x = 2
x = 1
b ) 4 ( x + 1 ) + 3 = 35
4 x + 4 + 3 = 35
4 x = 35 - 7
4 x = 28
x = 7
c ) 5 ( 2 x + 3 ) + 1 = 76
10 x + 15 + 1 = 76
10 x = 76 - 16
10 x = 60
x = 6
D ) 4 ( 2 x + 4 ) -10 = 54
8 x + 16 -10 = 54
8 x = 54 - 6
8 x = 48
x = 6
a)2(x+3)=8=8:2=4=(x+3)=x=1
b)35-3=32:4=8=(x+1)=x=7
c)76-1=75:5=15=2x=15-3=12:2=6
la d este6
b)35-3=32:4=8=(x+1)=x=7
c)76-1=75:5=15=2x=15-3=12:2=6
la d este6